DESLORATADINE IN TREATMENT OF ALLERGIC RHINITIS: RESULTS OF RANDOMIZED, PLACEBO_CONTROLLED TRIAL - R.T. Saygitov ("Paediatrician" Publishers LLC, 2008)
This review presents the results of randomized placebo controlled trial, aimed at studying the efficiency of modern non sedative antihistamine desloratadine in allergic rhinitis (AR). It is proven demonstratively that the application of desloratadine in comparison with placebo is accompanied by reduction in total symptoms scores, total nasal symptoms score and improvement in nasal airflow patency. In addition, the advantage of desloratadine versus placebo was established for reducing of nasal eosinophil levels. The acquired data confirm that the efficiency of desloratadine for AR corresponds to IA level of evidence.Key words: desloratadine, allergic rhinitis, randomizeplacebo_controlled trial.